Evolving strategic plan of action towards gender equality in the priesthood of the redeemed christian church of god, Nigeria - Olusola, A. I.; Ojo, M. Y. (Social Sciences, 2010)
This study examined strategy that could be developed to address the issue of gender inequality in the priesthood of the Redeemed Christian Church of God in Nigeria. Though in the church, women were included in the priesthood but there is no true representation especially at the highest cadre of the priestly hierarchy in terms of gender. The need for more women to participate in the priesthood is informed by the fact that women constitute majority in the population of the church. Using both the primary and secondary source of data collection, the findings of the research revealed that the highest level of the priesthood in RCCG is still largely controlled by men. Women are making steady progress as Parish, Area and Zonal Pastors, though the gap is still wide. Some of the factors that was identified as the reasons for the disparity include, the negative attitude of women, motherhood, genetics basis for sexual role and the culture of most ethnic group in Nigeria that is gender stereotyped. Based on the findings, a model of priesthood for offices and duties for females was proposed to improve female participation in the priesthood. The offices and duties to be allocated for female in the model was specified in order to solve some of the problems for poor representation of women in the priesthood. In the light of the study, it was recommended that the admission of women into the priesthood of RCCG would guarantee wholeness in Christ. The research also contended that Theological institutions and Tertiary Education should include gender issues in their curricula. © Medwell Journals, 2010.
Free
Keywords: Denomination; Gender; Leadership; Priesthood; Redeemed church; Scripture